2010
DOI: 10.1029/2010gl044999
|View full text |Cite
|
Sign up to set email alerts
|

Observation of non‐spherical ultragiant aerosol using a microwave radar

Abstract: Observations of ultragiant aerosol particles performed at the CNR‐IMAA Atmospheric Observatory using a Ka‐Band Doppler radar in four different periods from 19 April to 13 May 2010 are presented. In the reported cases, the aerosol radar signatures are characterized by a similar scenario. In particular, the linear depolarization ratio shows values higher than −4 dB probably related to the effect of bulk density and to the non‐sphericity of the ultragiant particles. During the same period, volcanic aerosol layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 16 publications
1
50
1
Order By: Relevance
“…Any decision support system for both civil F. S. Marzano et al: The Eyjafjöll explosive volcanic eruption protection and air traffic management needs not only a detection of the erupted and dispersed ash cloud, but also the estimation and forecast of its ash content (Prata and Tupper, 2009). The Eyjafjöll eruption on 2010 has been one of the best documented European volcanic events in terms of ground and satellite observations (e.g., Ansmann et al, 2010;Bennet et al, 2010;Flentje et al, 2010;Guðmundsson et al, 2010;Madonna et al, 2010;Mona et al, 2010;Schumann et al, 2011;Pietruczuk et al, 2010;Stohl et al, 2011). Particular importance is devoted to the "near-source" (where the "source" is the volcano vent) instrumentation as measured data can be used to properly initialized ash-plume dispersion models (e.g., Bonadonna et al, 2009;Costa et al, 2006;Stohl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Any decision support system for both civil F. S. Marzano et al: The Eyjafjöll explosive volcanic eruption protection and air traffic management needs not only a detection of the erupted and dispersed ash cloud, but also the estimation and forecast of its ash content (Prata and Tupper, 2009). The Eyjafjöll eruption on 2010 has been one of the best documented European volcanic events in terms of ground and satellite observations (e.g., Ansmann et al, 2010;Bennet et al, 2010;Flentje et al, 2010;Guðmundsson et al, 2010;Madonna et al, 2010;Mona et al, 2010;Schumann et al, 2011;Pietruczuk et al, 2010;Stohl et al, 2011). Particular importance is devoted to the "near-source" (where the "source" is the volcano vent) instrumentation as measured data can be used to properly initialized ash-plume dispersion models (e.g., Bonadonna et al, 2009;Costa et al, 2006;Stohl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 10b reveals that a fast increase of PM 10 and SO 2 mass concentrations occurred at ∼ 06:00 UTC on 20 April and that high peak SO 2 mass concentrations were reached earlier at site G than at site C, even though site G is further south than site C. The advection over south-eastern Italy of an inhomogeneous cloud of volcanic particles was likely responsible for these results. Volcanic particles were detected at the CNR-IMAA Laboratory which is ∼ 150 km away from site G, since the night of 19 April (Madonna et al, 2010;Mona et al, 2012) and back trajectory pathways reveal that the back trajectory ending on 20 April, 06:00 UTC at 100 m a.s.l. crossed the CNR IMAA Laboratory area before reaching site G.…”
Section: Unile Lidar Measurementsmentioning
confidence: 99%
“…Emeis et al (2011) found from remote sensing data and numerical simulations that the first volcanic ash layer reached Germany on 16 April. The volcanic ash was detected in clear layers above Switzerland starting from 17 April (Bukowiecki et al, 2011), above southern Italy from 19 April (Madonna et al, 2010;Mona et al, 2012), and over Greece after 21 April (Papayannis et al, 2012). The spatiotemporal distribution of the volcanic ash over Europe has been investigated extensively by EARLINET, the European Aerosol Research LIdar NETwork, which performed almost continuous measurements from 15 April to 22 May 2010 (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The observatory operates in a typical mountain weather environment strongly influenced by Mediterranean atmospheric circulation, resulting in generally dry, hot summers and cold winters, and is affected by a large number of Saharan dust intrusions each year (Mona et al 2006). CIAO represents the most equipped ground-based remote sensing station in the Mediterranean Basin for atmospheric profiling (see Table 29-1; Madonna et al 2011;Boselli et al 2012). Since 2000, CIAO is collecting systematic observations of aerosol, water vapor, and clouds.…”
Section: ) the Richard Assmann Observatory And German Observatory Nementioning
confidence: 99%